FinTech Megatrends: An Assessment of Their Industrial and Welfare Implications - Cho, Man (KDI School of Public Policy and Management, 2021)
This study aims to assess the industrial and welfare implications of FinTech as documented in the literature, by focusing on its four subsectors - online capital-raising platforms, alternative payment systems, AI and robot based investment consultancy, and alternative regulatory compliance service. Key findings obtained include: thanks to the advancement in the technologies of relevancy since the 1990s, the FinTech service providers have greatly enhanced both efficiency of financial intermediation and extent of financial inclusion in the developed as well as developing countries; these alternative financial service providers tend to narrow credit gap caused by information asymmetry between borrower and lender by collecting and utilizing soft data for ex ante credit evaluation; however, some concerns are also raised as to the likelihood of over-leverage by certain segments of P2P platform borrowers, the lack of appropriate skin-in-the-game arrangement in sharing ex post credit losses, and the inadequate consumer protection measures in the face of the heightened cyber-security risk. Based on these findings, an assessment is made as to whether or not the sector is capable of instituting a fullblown risk-based, or marginal-cost, pricing for embedded credit risk. In addition, one particular segment of the FinTech service providers, those affiliated with BigTech companies, is examined in terms of its potential contribution to social welfare not only through posing a heightened competition and contestability to existing financial institutions but also through innovation- and information-sharing among firms within their ecosystems. Included as the main contents in the study are trends and institutional characteristics of the four FinTech sub-sectors, financial theories of relevancy, the FinTech’s welfare implications, and the regulatory issues to be considered for the sector.
Keywords: Financial Innovation; FinTech(Financial Technology); BigTech; Market Place Lending; Crowdfunding; AI and Robo-advisor; RegTech